2016
DOI: 10.1121/1.4961014
|View full text |Cite
|
Sign up to set email alerts
|

Auditory sensitivity to local stimulation of the head surface in a beluga whale (Delphinapterus leucas)

Abstract: Using the auditory evoked response technique, sensitivity to local acoustic stimulation of the ventro-lateral head surface was investigated in a beluga whale (Delphinapterus leucas). The stimuli were tone pip trains of carrier frequencies ranging from 16 to 128 kHz with a pip rate of 1 kHz. For higher frequencies (90-128 kHz), the low-threshold point was located next to the medial side of the middle portion of the lower jaw. For middle (32-64 kHz) and lower (16-22.5 kHz) frequencies, the low-threshold point wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Generally, the middle parts of lower jaw (mandible) had the best hearing sensitivities. The rostrum tip just showed a relatively high sensitivity for middle-frequency (32 kHz-64 kHz) acoustic stimuli (Popov et al 2016). The simulations here introduced an alternative reception pathway for the target animal, but whether this pathway is responsible for the high hearing sensitivity at the rostrum tips of Beluga whale, Risso's dolphin and Yangtze finless porpoise still needs future studies to address.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Generally, the middle parts of lower jaw (mandible) had the best hearing sensitivities. The rostrum tip just showed a relatively high sensitivity for middle-frequency (32 kHz-64 kHz) acoustic stimuli (Popov et al 2016). The simulations here introduced an alternative reception pathway for the target animal, but whether this pathway is responsible for the high hearing sensitivity at the rostrum tips of Beluga whale, Risso's dolphin and Yangtze finless porpoise still needs future studies to address.…”
Section: Discussionmentioning
confidence: 95%
“…While the authors ascribe these lower hearing thresholds to hearing responses generated by both ears, an additional hypothesis is that the good hearing sensitivity at rostrum tip might be related to the bone conduction in current paper. In a recent study, Popov et al (2016) concluded the sound conduction to the auditory system is frequency dependent. The areas of best sensitivity shifted when the frequency of the acoustic stimuli changed.…”
Section: Discussionmentioning
confidence: 99%
“…Cranford et al developed a numerical model of a Cuvier’s beaked whale ( Ziphius cavirostris ) and found an additional sound entrance through the ventral margin of the mandible [ 15 ]. The solid mandible was thought to be an important guide to conduct sounds to the bony complexes as well, as demonstrated in auditory examinations on beluga whales ( Delphinapterus leucas ), indicating a high sensitivity to sound stimulation from the rostrum tip [ 22 , 23 ]. This location might also be the entrance of the effective acoustic channels for the Risso’s dolphin ( Grampus griseus ) and the Yangtze finless porpoise ( Neophocaena phocaenoides asiaeorientalis ) [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These aggregations showed the complexity of acoustic windows in odontocetes. Though the most sensitive areas (the positions of acoustic windows) may have been demonstrated in many species [ 22 , 23 , 24 , 25 , 27 ], there might be other sound-reception paths that have not been addressed in detail as well as the roles of the various structures in these paths. The head as a whole may be considered a volume antenna [ 15 , 27 ], and thus, the roles of the various structures, including the mandible, the mandibular fats, soft tissue, and skull, in conducting sounds to the ear complex require additional work to elucidate.…”
Section: Introductionmentioning
confidence: 99%